Rekonstruksi Regulasi Keotentikan Akta Notaris dalam Penggunaan Tanda Tangan Elektronik pada Pelayanan Kenotariatan di Indonesia - Karinawati Karinawati; Ifrani Ifrani (Lembaga Yasin AlSys, 2026)
Although electronic signatures have been legally recognized in Law Number 11 of 2008 concerning Electronic Information and Transactions, legal certainty regarding the authenticity of Notarial deeds using electronic signatures in Indonesia still faces regulatory harmonization issues. This study aims to analyze the legal synchronization between conventional and digital systems in the signing of Notarial deeds and to formulate an ideal regulatory construction for the development of electronic signatures in notarial services in Indonesia. This study employed normative legal research with a prescriptive-analytical type through statutory, conceptual, and comparative legal approaches. Legal materials were collected through a literature study covering primary, secondary, and tertiary legal materials, and were then analyzed using legal interpretation, synchronization, and harmonization techniques. The results showed horizontal disharmony between Article 16 paragraph (1) letter m of the Notary Position Law, which requires the physical presence of the parties in the reading and signing of deeds, and Article 11 of the Electronic Information and Transactions Law, which recognizes the validity of electronic signatures based on the principle of functional equivalence. Certified electronic signatures, electronic certificates, and digital verification systems have fulfilled the functions of authentication, identification, integrity, and non-repudiation. However, the unmet requirement of physical presence may cause electronic deeds to lose their authentic nature. This finding contributes to the development of notarial science and cyber law, particularly in understanding the transformation of notarial services in the digital era. The conclusion of this study emphasizes the importance of regulatory harmonization through the revision of the Notary Position Law to accommodate virtual presence and the use of certified electronic signatures. The implications of this study include theoretical contributions to the development of notarial law and cyber law literature, as well as practical implications for the government, the Indonesian Notary Association, and Notaries in formulating policies for the digitalization of notarial services. This study also opens opportunities for further research on the implementation of digital identity systems and data protection in cyber notary practice.